Activated Carbon Derived from Phoenix dactylifera (Palm Tree) and Decorated with MnO2 Nanoparticles for Enhanced Hybrid Capacitive Deionization Electrodes. Issue 11 (17th March 2020) - Govindan, Bharath; Alhseinat, Emad; Darawsheh, Ismail F. F.; Ismail, Issam; Polychronopoulou, Kyriaki; Jaoude, Maguy Abi; Arangadi, Abdul F.; Banat, Fawzi
Abstract: In this study, the electro‐sorption capacity and selectivity of activated carbon (AC) electrodes, produced from the leaf base of Phoenix dactylifera (palm tree) waste, are modified by enabling the reversible intercalation/conversion of sodium ions through the presence of nanoscale α‐MnO2 particles acting as redox mediators. The α‐MnO2 nanoparticles (NPs) are hydrothermally grown on the AC powder to obtain a functional composite material (α‐MnO2 /f‐AC). The morphological, textural, and physicochemical surface properties of the pristine and modified AC materials are thoroughly examined and correlated with the electrochemical performance of the resulting electrodes that are implemented in an asymmetric capacitive deionization (CDI) cell configuration (i. e. capacitive vs Faradaic electrodes). The pristine biowaste‐derived AC presents a high specific surface area of 1224 m 2  g −1, and high electrical capacitance of 259 F g −1 at 10 mV s −1 . The α‐MnO2 surface modification approach of the pristine material retains its large accessible surface area, and additionally enables a 50% increase in its specific capacitance value. The incorporation of the α‐MnO2 /f‐AC material in the anode and the pristine source in the cathode produces superior electrosorption capacity, as high as 17.8mgg −1 in batch‐mode CDI tests with 600mg L −1 NaCl feed. The enhanced electrical performance and pseudocapacitive behavior of the CDI cell can be explained by the α‐MnO2 nanoparticles playing a critical role in enabling a synergistic redox‐based charge‐discharge pathway under conditions compatible with the voltage operation requirements of the CDI process. Abstract : Activated carbon (AC) electrodes, produced from the leaf base of Phoenix dactylifera (palm tree) waste were used to remove ions from salian water using capacitive deionization. The pristine biowaste‐derived AC presents a high specific surface area of 1224 m 2  g −1, and high electrical capacitance of 259 F g −1 at 10 mV s −1 and showed excellent elctrosption capacity of 17.8 mg g −1 in a 600 mg L −1 initial NaCl concentration at 1.2 V with a flow rate of 10 mL min −1 .